Community empowerment for poverty alleviation through social entrepreneurship based on an ecological framework - Suyono, Hadi; Safaria, Triantoro (Empathy : Jurnal Fakultas Psikologi, 2024)
This study is rooted in the issue of poverty, which has the potential to incite conflicts. In response to this, the research aims to explore social entrepreneurship as a tool for community empowerment to alleviate poverty and prevent conflicts. The research adopts a qualitative approach with a phenomenological design. The participants include village heads, leaders of cooperatives, tourism awareness groups, ecotourism managers, youth organization members, representatives of the village consultative body, cooperative administrators, managers of village-owned enterprises, neighborhood leaders, and village heads. These participants were selected through purposive sampling. Data were collected via semi-structured interviews, and the data analysis employed thematic analysis, with member checking used to ensure validity. The findings indicate that social entrepreneurship through ecotourism business units, underpinned by an ecological framework, has been successful in fostering contributions from individuals, microsystems, organizations, local communities, and the macrosystem. This approach to empowerment has proven effective in reducing poverty and preventing conflicts.